Analysis of the ELT Pre-Services Teacher Lesson Plan: A Case on the Vocabulary Discussion - Elismawati Elismawati; Saunir Saun; Arwemi Arwemi; Hadeli Hadeli; Hidayat Alazmi (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
As the lesson plan is considered of main requirements for both teacher and practiced teacher and vocabulary discussion is essential to include. This research is aimed to identify the vocabulary discussion used by teacher in the Lesson Plan. Using 22 peaces ELT ELT lesson plan, the research was done by implementing documentation study. Regarding the distinction indicators of both KTSP and K13 curriculum, it was found that the lesson have some limitation in using the vocabulary discussion in which there are only 9.09% of the lesson plan that included the vocabulary discussion as a step in the teaching of reading for comprehension before doing reading activity, and 4.55% offers it after the students read the text. Most of the documents do not include the steps of vocabulary discussion in the teaching of reading for comprehension. Finally, 19 or 86.36% that did not offer the vocabulary discussion.